Effect of meteorological factors and growing media on growth in Houttuynia cordata Thunb - Kasemsan, Waraphol; Thongnumchaima, Yanitsa; Charoenphon, Sakda; Pramual, Panuchai; Kongsorn, Chatupol; Maksuwan, Atirat (Journal of Vocational Education in Agriculture, 2024)
This study aims to examine the meteorological factors affecting the growth of Houttuynia cordata Thunb and investigate the growing medium for the production of Houttuynia cordata Thunb. by analysing the relative/opposition for the correlation of spearman rank correlation coefficient between two meteorological factors. Analyzing the average line of the correlation between two meteorological factors from the linear regression equation. Meteorological differences were tested with Friedman's hypothesis test. After that, the effects of growing mediums were employed a completely randomized design (CRD) with 3 treatments and 6 replications including; (T1) surface soil:cow dung: rice husk (2:3:5) and fermented bioextracts from fresh fruit (T2) surface soil:cow dung:rice husk (2:3:5) and fermented bioextracts from banana shoots (T3) surface soil (control). Test the difference in the number of leafs, increased number of leafs and the number of plant saplings from the Houttuynia cordata Thunb roots by statistically testing the hypothesis of Kruskal – Wallis. The results showed that light intensity and air temperature had a high opposite correlation with statistical significance at the 95% confidence level. The state of meteorological factors was neutral equilibrium in nursery houses, causing the air temperature inappropriate for the growth of Houttuynia cordata Thunb. Number of leaves: The number of leaves increased. And the number of new saplings emerging from the flow of Houttuynia cordata Thunb is not significantly different at the 95 percent confidence level. From the research results, in addition to knowing inappropriate meteorological factors and the efficiency of using materials, Planted together with biological fermentation that has an effect on the growth of plum kao. It also provides guidelines for developing technology to control meteorological factors suitable for the growth of Houttuynia cordata Thunb, according to further recommendations.